The Attitudes, Stances, and Strategies of Different Legal Systems in Late Qing and Republican China Toward Catholic “Property Acquisition” - KANG, Zhijie (Journal of Research for Christianity in China (JRCC), 2025)
The signing of unequal treaties in modern times provided legal safeguards for Catholic activities in China. Catholic religious orders and dioceses began acquiring property on a large scale, thereby establishing the material foundation for the development of church affairs. However, academic research has not comprehensively examined how these unequal treaties defined the scope and procedures for foreign religions to “acquire property,” nor the obstacles encountered in implementing different treaties over time. and how the Chinese government adjusted relevant legal provisions over time. This paper analyzes laws and regulations concerning Catholic property acquisition during the late Qing and Republican periods (including the Sino-French Treaty of Beijing, the Berthier-Meyer Agreement, and the Provisional Regulations on the Lease of Land and Buildings by Foreign Churches in the Interior), thereby revealing another facet of Chinese Catholic history.